Analisis Pertumbuhan Pengguna Aplikasi Gemini Menggunakan Analisis Time Series Dengan Metode ARIMA - Ritzy Effendy; Marcell Fernando Wongso; Noval Saputra; Dicky Pratama (GLOBAL SCIENTS PUBLISHER, 2026)
This study examines the growth dynamics of Gemini app users, a strategic issue in the global artificial intelligence market competition. The primary objective is to project monthly active user (MAU) trends to identify potential market saturation phases. The methodology employs AutoRegressive Integrated Moving Average (ARIMA) modeling based on historical data from 2025 to early 2026. Analysis reveals that following a period of exponential growth driven by Android ecosystem integration, the rate of user acquisition has begun to undergo structural stabilization. Model predictions indicate that user numbers will reach a saturation point of approximately 860 million MAU by the end of the third quarter of 2026. These findings suggest an industry-wide shift in focus, moving away from mass acquisition toward user growth strategies fueled by future digital innovation.